2000
DOI: 10.1177/0957926500011001005
|View full text |Cite
|
Sign up to set email alerts
|

Demanding Respect: The Uses of Reported Speech in Discursive Constructions of Interracial Contact

Abstract: This investigation examines discursive uses of respect in talking about interracial contact. In discussing the documentary, Racism 101, the most frequently quoted portion by African-American and Latino participants was a segment on demanding respect from Whites. Our first study analyzes such discourse-reported speech-for what is made relevant from the original documentary segment. The participants' reported speech conveys little of the exact wording of the original, but does capture its spirit through using si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 18 publications
0
44
0
Order By: Relevance
“…This is also a generalised formulation which appeals to shared knowledge about the existence of this familiar, repeated form of racism. The recreation of direct reported speech here simultaneously lends empirical support to the observation (such questions plausibly do occur in reality), and functions to signal the negative evaluation of the reported speaker's views (see also Buttny 1997;Buttny and Williams 2000;Holt 2000;Stokoe and Edwards 2007). The functions of reported speech will be elaborated later in the paper.…”
Section: Common Sensementioning
confidence: 86%
“…This is also a generalised formulation which appeals to shared knowledge about the existence of this familiar, repeated form of racism. The recreation of direct reported speech here simultaneously lends empirical support to the observation (such questions plausibly do occur in reality), and functions to signal the negative evaluation of the reported speaker's views (see also Buttny 1997;Buttny and Williams 2000;Holt 2000;Stokoe and Edwards 2007). The functions of reported speech will be elaborated later in the paper.…”
Section: Common Sensementioning
confidence: 86%
“…Previous research shows that reported speech often serves the purpose of creating evaluative portraits of the quoted people (Buttny 1997;Hall et al 1999;Buttny and Williams 2000). Making negative evaluations of people is common for complaints accomplished through reported speech (Drew 1999;Stokoe and Edwards 2007).…”
Section: Making Negative and Positive Portraits Of Clientsmentioning
confidence: 99%
“…What Buttny (1997) and Buttny and Williams (2000) suggest in their analysis of reported speech in focus groups discussing race can also be traced in another report, this time with a more positive assessment or positioning, though difficult again to attribute. The news is entitled Policiais militares são acusados de racismo contra garoto de 12 anos -PM teria ofendido menino negro em supermercado (Police officers are accused of racism against a 12 year old boy Police officers allegedly offended Black boy in a supermarket).…”
Section: Defines As Interdiscursivity In Genresmentioning
confidence: 99%
“…On the one hand, the collocation could have been used by the girl herself. On the other, it could be interpreted as assessment or positioning (Buttny, 1997;Buttny and Williams, 2000) of the newspaper which, I argue, underestimates the issue when framing the student s attitudes to racism as instructions in a recipe.…”
Section: Defines As Interdiscursivity In Genresmentioning
confidence: 99%